Decreased SFRP5 correlated with excessive metabolic inflammation in polycystic ovary syndrome could be reversed by metformin: implication of its role in dysregulated metabolism - Yi Zhang; Yuxin Ran; Lingna Kong; Lihong Geng; Hua Huang; Hongying Zhang; Jun Hu; Hongbo Qi; Ying Chen (BMC, 2021)
Abstract Background Polycystic Ovary Syndrome (PCOS) is a complex endocrine disorder of heterogeneous nature. Secreted frizzled-related protein (SFRP) 5 is an anti-inflammatory adipokine implicated in metabolic homeostasis. We aimed to confirm the correlation between SFRP5, metabolic inflammation and PCOS, investigate the predictive value of SFRP5 for PCOS and the involvement of SFRP5 in metformin treated PCOS. Methods This retrospective case-control study included 140 PCOS and 33 control women. Sixty seven PCOS women were included for detecting serum SFRP5 level and its correlation with metabolic inflammation. Predictive value of SFRP5 for PCOS was evaluated by logistic regression and receiver operating characteristic (ROC) analyses. Seventy three PCOS women complicated with impaired glucose tolerance (IGT)/insulin resistance (IR) were included for investigating the effects of metformin (37 with metformin vs. 36 without metformin) on SFRP5, pro-inflammatory cytokines, ovulation and pregnancy rate. Results Plasma SFRP5 levels were decreased in PCOS (odds ratio: 0.78, 95% confidence interval (CI):0.703-0.866, P < 0.001) independent of obesity. SFRP5 was negatively associated with IL-6, TNFα, FAI and HOMA-IR. The cut-off point of SFRP5 < 46.13 ng/ml was optimal to identify PCOS with a higher specificity of 96.87% and a relatively lower sensitivity compared to AMH. SFRP5 increased specificity of AMH for predicting PCOS, especially which with relatively decreased AMH (< 4.7 ng/ml). Metformin promoted SFRP5 and decreased leptin, IL-6 and TNFα secretion in PCOS women with metabolic abnormality in a time dependent manner and with improved ovulation rate and pregnancy rate. Conclusion Decreased SFRP5 was associated with metabolic inflammation in PCOS and has a potential role for the supplement of AMH in predicting PCOS. The reverse of serum SFRP5 by metformin indicated that SFRP5 participated in the improvment of follicular development by metformin. Further prospective investigations are needed to confirm these preliminary data.